Manual der Koloproktologie, Band 1 - Herold, Alexander; Schiedeck, Thomas (De Gruyter, 2019)
This is the standard textbook for every medical or surgical coloproctologist from the German Society for Coloproctology. In two volumes, it covers the full anatomy of the colon from the ileocecal valve to the anus. Each chapter offers a comprehensive overview of the etiology, pathogenesis, classification, symptomatology, diagnosis, conservative and surgical therapy, and the prophylaxis of individual diseases.